Molecular markers in the genetic analysis of crossability of bread wheat with rye - I. V. Porotnikov; O. Yu. Antonova; O. P. Mitrofanova (Вавиловский журнал генетики и селекции)
Bread wheat (Triticum aestivum L.), the varieties of which are widely used for the grain production, is difficultly crossable with related species of Triticeae Dum. This factor limits the chance of introduction of alien genetic material into the wheat gene pool and the possibility of new varieties breeding with good adaptation to adverse environmental factors. The crossability between wheat and related species is controlled by Kr1-Kr4 genes (Crossability with Rye, Hordeum and Aegilops spp.) and the SKr gene (Suppressor of crossability). SKr and Kr1 have the largest influence on the trait. In the case of the recessive alleles, these genes do not function and the quantity of hybrid seeds after pollination with alien species can achieve more than 50 %. SKr is located on 5BS between the GBR0233 and Xgwm234 markers, closely linked with the markers Xcfb341, TGlc2 and gene12. Kr1 was mapped on 5BL, proximally to the Ph1 gene, between the EST-SSR markers Xw5145 and Xw9340. The markers of SKr were used to control the transfer of its recessive allele into other wheat genotypes, which made it possible to obtain highly crossable forms. However, the advantages of using the SKr and Kr1 markers in marker-assisted selection and in the screening of ex situ collections are not sufficiently studied. The published Kr1 sequence for varieties with different crossability offers great prospects, because it will be possible to create allele-specific markers. In this review, the following issues are considered: genetic resources created by wheat and rye hybridization, the geographical distribution of easy-to-cross forms of wheat, genetic control of the wheat and rye compatibility, advances of the use of molecular markers in the mapping of Kr-genes and their transmission control.